Do environmental temperatures and altitudes affect physical outputs of elite football athletes in match conditions? A systematic review of the 'real world' studies. Issue 1 (2nd January 2023) - Draper, Garrison; Wright, Matthew D.; Ishida, Ai; Chesterton, Paul; Portas, Matthew; Atkinson, Greg
ABSTRACT: Players involved in the various football codes compete throughout the calendar year around the world. Therefore, environmental stressors such as temperature and altitude should be considered in preparation for, and during, matches. We aimed to systematically review the observational and quasi-experimental studies that have been specifically designed to quantify the effects of temperature (hot or cold) high altitude on in-match physical performance indicators. A search of electronic databases (Web of Science, Scopus, SPORTDiscus, PubMed/MEDLINE) was conducted, with 19, 424 papers identified as relevant. Following sifting in relation to the eligibility criteria, 12 papers were deemed directly relevant. The reviewed studies scored 6–9 (on a 0–9 scale) for quality assessment using a previously used scale. The major outcome variables relevant to the current review were total distance (m), high-speed running (m) and high-speed runs (count) measured during matches. Standardized effect sizes (ES) were heterogeneous across studies for total distance (ES: −0.96 to −0.14) and high-speed running (ES: −0.69 to 0.12) for >1000 m vs sea-level, time spent at the given altitude being a putative factor for this heterogeneity. Heat had mainly detrimental effects on performance, but ES were, again, heterogeneous across studies (ES: −1.25 to 0.26), dependent on temperature. Given the small number of studies that involved mostly male athletes, and large heterogeneity across studies, more research needs be conducted on physical performance in these environmental conditions, with attention paid to standardizing outcomes and broadening the approaches of studies to guide future decision-making in professional sporting environments.